Dietary selenium peptide supplementation for increasing the growth of African catfish Clarias gariepinus - Muhammad Agus Suprayudi; Muhammad Roikhan Amanullah; Dedi Jusadi; Hasan Nasrullah; Ahmad Yazid Latif (Jurnal Akuakultur Indonesia, 2023)
Selenium is an essential micromineral that the body needs in modest amounts (0.2–12 mg/kg), yet it has important effects on the antioxidant defense, immune system, and digestive performance of aquatic species. This study aimed to analyze the growth of catfish (Clarias gariepinus) supplemented with feed additives containing selenium peptide through the coating method on feed. There were four different treatments, namely K (feed without feed additive), and feed with additive supplementation: A (3 g/kg feed), B (6 g/kg feed), and C (9 g/kg feed). A total of 15 catfish at an initial weight of 21.80 ± 0.29 g were reared in a 90×40×45 cm3 aquarium filled with water at a volume of 108 L, for 45 days. Fish were fed three times a day at satiation. Water quality management was carried out by the use of simple filtration in the container and water replacement to ensure optimum water quality values for catfish growth. The results showed that the final biomass of catfish fed with selenium peptide was significantly different (p<0.05) from catfish fed without selenium peptide, with a value of 1147,50 g and 96,67% of survival rate. Based on this study, the best dose of feed additive in catfish feed was 3 g/kg of feed. Keywords: Clarias gariepinus, growth, selenium peptide ABSTRAK Selenium adalah mikromineral esensial yang dibutuhkan tubuh dalam jumlah sedikit (0,2–12 mg/kg), akan tetapi sangat berperan dalam sistem anti-oksidatif, imunitas, dan kinerja pencernaan pada organisme akuatik. Penelitian ini bertujuan menganalisis pertumbuhan ikan lele (Clarias gariepinus) yang ditambahkan dengan feed additive mengandung selenium peptida melalui metode coating pada pakan. Terdapat empat perlakuan berbeda, yaitu K (pakan tanpa selenium peptida), dan pakan dengan suplementasi feed additive: A (3 g/kg pakan), B (6 g/kg pakan), dan C (9 g/kg pakan). Ikan lele ukuran 21,80 ± 0,29 g sebanyak 15 ekor dipelihara dalam akuarium berukuran 90×40×45 cm3 dengan total volume air 108 L, selama 45 hari. Ikan diberi pakan tiga kali sehari secara at satiation. Pengelolaan kualitas air dilakukan dengan filtrasi sederhana serta penggantian air untuk memastikan kualitas air optimal untuk pertumbuhan ikan lele. Hasil penelitian menunjukkan biomassa akhir ikan lele dengan suplementasi selenium peptida pada pakan berbeda nyata (p<0,05) dibandingkan dengan kontrol dengan nilai bobot sebesar 1147,50 g dan kelangsungan hidup 96,67%. Berdasarkan penelitian ini, dosis terbaik feed additive yang mengandung selenium peptida adalah 3 g/kg pakan pada ikan lele. Kata kunci: Clarias gariepinus, pertumbuhan, selenium peptida